Spatial Variation of Traffic Accidents Recorded in the City of Al-Amirah, Southern Iraq (Eurasian Journal of History, Geography and Economics, 2022)
The study addressed the definition of traffic accidents as well as the incidents by their types, and found that they are classified into three categories, but that collisions, which ranked first by (730) collisions of all accidents recorded in the city of Amarah during the length of the study (2010-2020) or accidents of coup or run over, and showed a discrepancy in the number of accidents between the years covered, It was the highest rate in 2012 with a total of 136 incidents, Monthly, April had the highest accident rate with 88 accidents, and accident-causing vehicles varied between cars and motorcycles of all types, and the study divided the city streets into four categories according to the number of accidents, and a group of streets where accidents were concentrated, indicating a discrepancy in the spatial distribution of accidents within the study area, and the study identified a number of factors that exacerbated the problem of accidents in the study area. The study concluded with a number of results and recommendations that the researchers hope will be implemented to address the problem of traffic accidents in Amarah